A Case Study of Nanofiltration Using an Irreversible Thermodynamics-Based Model. (2nd February 2012) - Vakili-Nezhaad, G. R.; Akbari, Z.
Abstract : The extended Spiegler-Kedem model that can be solved by using genetic algorithm (GA) has been used for study of the rejection of charged and uncharged solutes in a nanofiltration process. In this work, the accuracy and applicability of this model were tested with the data obtained from the nanofiltration of a real solution. The permeated solution was obtained from the whey ultrafiltration system (ultrafiltered whey). The studied process separates lactose and mineral salts from ultrafiltered whey. Moreover, the ultrafiltered whey nanofiltration system has been simulated with higher precision compared to the other sources of existing data.